(untitled) (Journal Of Educational and Psychological Researches, 2025)
This research aims to reveal the extent to which the content of Omani science textbooks for grades 5–10 includes both the indicators of the seven objectives of the Priority of Environment and Natural Resources in Oman Vision 2040 and the requirements of environmental knowledge. The descriptive methodology was employed in analysing the content of 12 school science textbooks for grades 5–10, using a content analysis schedule that included 26 indicators of the seven objectives of Environment and Natural Resources Priority. By processing the data resulting from the analysis process using descriptive statistics, the results showed that the content of science textbooks for grades 5–10 includes only four objectives (1st, 2nd, 3rd, and 6th) of Environment and Natural Resources Priority. Regarding environmental knowledge, the results showed that the content of the analysed science textbooks is highly embedded with attributes, while environmental statistics were the least included. According to these findings, the study recommended increasing the degree of inclusion of all seven objectives of Environment and Natural Resources Priority and their indicators in Omani science textbooks for grades 5–10.